Rapid and quantitative detection of C-reactive protein based on quantum dots and immunofiltration assay - Zhang, Pengfei (Int J Nanomedicine, 2015)
Convenient and rapid immunofiltration assays (IFAs) enable on-site “yes” or “no” determination of disease markers. However, traditional IFAs are commonly qualitative or semi-quantitative and are very limited for the efficient testing of samples in field diagnostics. Here, we overcome these limitations by developing a quantum dots (QDs)-based fluorescent IFA for the quantitative detection of C-reactive proteins (CRP). CRP, the well-known diagnostic marker for acute viral and bacterial infections, was used as a model analyte to demonstrate performance and sensitivity of our developed QDs-based IFA. QDs capped with both polyethylene glycol (PEG) and glutathione were used as fluorescent labels for our IFAs. The presence of the surface PEG layer, which reduced the non-specific protein interactions, in conjunction with the inherent optical properties of QDs, resulted in lower background signal, increased sensitivity, and ability to detect CRP down to 0.79 mg/L with only 5 µL serum sample. In addition, the developed assay is simple, fast and can quantitatively detect CRP with a detection limit up to 200 mg/L. Clinical test results of our QD-based IFA are well correlated with the traditional latex enhance immune-agglutination aggregation. The proposed QD-based fluorescent IFA is very promising, and potentially will be adopted for multiplexed immunoassay and in field point-of-care test.